Internet Management: Value and Need - Arora, Aman (Journal of Information and Knowledge, 2002)
As the size of Internet is increasing. so is the intricacy in managing Internet. This paper is an attempt to provide the critical issues that give rise to the need for Internet management and the attempts being made throughout the world in this direction. The Internet management components and the functions are also discussed.